THE EFFECT OF SYARIAH BUSINESS ON INDONESIA CRYPTOCURRENCY 2022 - Afrizal Ramadhan Siregar (SEAN Institute, 2022)
Digital assets that are traded in cyberspace or known as cryptocurrency where the value soars and fluctuates, are influenced by buying and selling requests. Where Cryptocurrency is virtual money, digital money, or electronic money that is in cyberspace and does not have a concrete object form. There are many types of cryptocurrencies, including Litecoin, Monero, Ether, Ripple, Ethereum, Qtum, Dash, Zcash, and Bitcoin. also seen from an Islamic point of view, so it raises research questions about how cryptocurrency law is in Islamic law. The applied theory used is the business taxonomy of haram lidzatihi and haram lighairihi from a large number of scholars reconstructed by Adiwarman Abdul Karim. This research is a literature study. The data sources for this research were taken from the Koran, Rasulullah's hadith, and classic and contemporary books, as well as from online media sources.